Does earnings management influence dividend policies? An approach with unlisted firms - Lopes, A.I.; Narciso, A. (20º USP International Conference in Accounting, 2020)
The goal of this paper is to analyze whether the firms’ dividend policy is influenced by the existence of earnings management practices, particularly under different ownership contexts. In the paper, three well-known discretionary accruals methodologies are applied to measure earnings management. The empirical study relies on an innovative set of 4,258 unlisted private companies, representing a panel of around 20 thousand observations distributed over the period 2013-2017. The study is focused only in one European country to avoid different institutional and country characteristics that could bias the findings. Our firs result reveals a positive statistically significant relationship between the earnings management and dividend policy, meaning that private non-listed companies managing earnings are more likely to distribute a higher level of dividends. However, a deeper analysis shows that the ability of earnings management practices to predict the dividend policy is driven by ownership concentration. Spliting the sample, we find that the positive influence of earnings management on dividend policy in non-listed private companies is statistically significant only in companies whose shareholders have control (more than 50% of share capital) as opposed to firms with non-concentrated ownership. Our results contribute for the literature around the quality of financial reporting, lengthening these thematic to include non-listed companies.